Evaluasi Kualitas Layanan Kedai Kopi Melalui Model IPA-Kano - Dea Arivah Amelia; Wandhansari Sekar Jatiningrum (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
Coffee consumption has become the lifestyle of today’s society. This was used by a number of business people to start a coffee shop business. Consumers not only to enjoy the taste of coffee but also a comfortable atmosphere. Therefore, coffee shop businesses in Indonesia were going escalated. Thus, competition between similar businesses was increasing rapidly. This was occurred at ABC Coffee Shop in Cirebon. Cirebon has a high market potential although it is a small city. This research aimed to evaluate service quality in ABC Coffee Shop in order to obtain appropriate business strategies. Data collection was carried out by distributing questionnaires related to service quality to 100 ABC Coffee Shop consumers. Analysis was conducted by IPA-Kano model. Results showed that attributes need to be improved sequentially were interior and exterior design, cleanliness of toilets and quality of taste, self confidence and attitude to serve consumers, and completeness of facilities, speed for serving menus and sincerity of employees to respond consumers